One‐piece zirconia oral implants: one‐year results from a prospective case series. 2. Three‐unit fixed dental prosthesis (FDP) reconstruction. (18th March 2013) - Kohal, Ralf‐Joachim; Patzelt, Sebastian B. M.; Butz, Frank; Sahlin, Herman
Abstract Aim To evaluate the clinical and radiological outcome of one‐piece zirconia oral implants for three‐unit fixed dental prosthesis (FDP) replacement after 1 year. Materials Twenty eight patients were recruited for the investigation and signed an informed consent. All patients were treated with a one‐stage implant surgery and a three‐unit immediate temporary restoration on two one‐piece zirconia implants. The implants were fabricated of yttria‐stabilized tetragonal zirconia (y‐TZP). The endosseous part of the implants was tapered with a porous surface. A total of 56 implants were inserted in the 28 patients. A total of 12 implants were placed in the upper jaws (six in the anterior area and six in the posterior area) and 44 in mandibles (all in the posterior area). At implant insertion and after 1 year, standardized radiographs were taken to evaluate the peri‐implant bone loss. To evaluate any influences from different baseline parameters on the marginal bone loss a univariate analysis was performed. Clinical soft tissue parameters probing depth (PD), clinical attachment level (CAL), modified bleeding index (mBI) and modified plaque index (mPI) were recorded. Implant cumulative survival rates were calculated using actuarial life table analysis. Changes in the clinical variables were assessed using the Wilcoxon Signed Ranks test (PD, CAL) and the Sign test (mBl, mPl). All significance tests were conducted at a 5% level of significance. Results After 1 year, one implant was lost resulting in a survival rate of 98.2%. The patient was excluded from further analysis. The marginal bone loss after 1 year amounted to 1.95 mm. In 40% of the patients a bone loss of at least 2 mm and in 28% of the patients a loss of more than 3 mm were observed. The PD decreased for implant and tooth sites over time, the values being significantly higher for implants than for teeth. Over 1 year, the CAL increased slightly around the implants and decreased around the teeth. At the 1‐year follow‐up, the CAL at the implant sites was statistically significantly higher than at the reference teeth. The mBI was significantly lower at implants than at teeth. The same result was found for the plaque index. Conclusions A high frequency of increased radiographic bone loss (>2 mm) after 1 year around the presented one‐piece zirconia implant system was found. The bone loss seems to be higher compared to the very limited availability of zirconia implant data. Therefore, within the limits of the present investigation, it may be concluded that the presented zirconia implant system possibly performs inferior to conventional titanium implants and to other zirconia implants regarding peri‐implant bone loss.